HUBUNGAN KEPATUHAN REHABILITASI MEDIK DENGAN DERAJAT KECACATAN PADA PENDERITA PASCA STROKE DI INSTALASI REHABILITASI MEDIK RSUP Dr. MOH. HOESIN PALEMBANG - Rini, Puji Setya (IKesT Muhammadiyah Palembang, 2013)
Stroke insidens in Indonesia is 200 from 100.000 populations. In one year from 100.000 populations, 200 people will get stroke. In Indonesia stroke is in third level from deathly diseases after heart disease and cancer. According survey 2004, the killer number one is stroke in government hospital all around Indonesia. According WHO, rate of disability cause stroke about 50 until 60 percent from stroke prevalency. One per five until a half of stroke suffers can do daily activities without help but quarter until two per three suffers of stroke get permanent disable. The lack of ability functional can be decreased by doing rehabilitation started during two days after stroke attack and it should be continued after go out from hospital. Commonly recovery of interference neuron on stroke happens in the first week.The objective of this study is to know the correlation obedient of medic rehabilitation with level of disability on pasca stroke suffers in Instalasi Rehabilitasi Medik RSUP Dr. Moh. Hoesin Palembang. The method that is used in this research by using design of correlation study by approaching cross sectional, the total of sample as many thirty four people which suitable with inclution criteria. The collecting data was done by using questioner and data analyze done with univariate, bivariate and multivariate. The results of logistic regression multivariate are two the most variables which influenced to the obedience in doing medic rehabilitation, namely incoming (B=3,036 dan p value = 0,019) and supporting family (B=2,616 dan p value =0,013). Nurses as one of healthy employees indirectly have correlation with pasca stroke suffers. One of roles nurses is as researcher and can be hoped identificated the research problem and use the result of research to increase the service and nursing education in order the result of research can be referenced in giving nursing of pasca stroke suffers